2020
DOI: 10.3390/ijerph17238811
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of Fermented Oyster-Derived Lactate on Exercise Endurance Indicators in Mice

Abstract: Exogenous lactate administration has more recently been investigated for its various prophylactic effects. Lactate derived from potential functional foods, such as fermented oyster extract (FO), may emerge as a practical and effective method of consuming exogenous lactate. The current study endeavored to ascertain whether the lactate derived from FO may act on muscle cell biology, and to what extent this may translate into physical fitness improvements. We examined the effects of FO in vitro and in vivo, on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Lactate is known to have antioxidant effects by modulating Nfr2 and reduced cell death which is induced by ROS [ 44 ]. Through the specialized fermentation process, the oyster extract has enriched GABA and lactate, increasing the oyster’s bioactive properties [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lactate is known to have antioxidant effects by modulating Nfr2 and reduced cell death which is induced by ROS [ 44 ]. Through the specialized fermentation process, the oyster extract has enriched GABA and lactate, increasing the oyster’s bioactive properties [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…FO extract was obtained from Marine Bioprocess Co., Ltd. (Gijang, Busan, Korea). For extraction, FO was prepared by fermentation with Lactobacillus brevis BJ20 [ 29 , 45 , 62 , 63 , 64 ], and glutamic acid and dextrin were used on behalf of monosodium glutamate and an excipient, respectively. Glutamate was used as a precursor to producing GABA through a decarboxylation reaction for fermentation with Lactobacillus brevis BJ20 [ 45 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also contain a large amount of phosphorus taurine (based on a 4.2%/dry base) and represent one of the world’s top 10 seafood foods rich in essential minerals such as glycogen, vitamins, iron, and iodine ( 6 ). Recently, the effects of lactic acid-fermented oyster extract (FO) containing GABA and lactic acid, produced by lactic acid fermentation of oysters, on bone formation ( 7 ), height growth ( 8 ), and exercise performance improvement ( 9 ) have been reported. Also, a previous study showed that GABA-enriched FO reduced muscle proteolysis by increasing mRNA levels of IGF-1 expression in dexamethasone-treated animals ( 10 ).…”
Section: Introductionmentioning
confidence: 99%